ANALISA FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI NON ASN DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SITUBONDO DENGAN EFEKTIVITAS KERJA SEBAGAI MEDIASI VARIABEL - Putri, Septi Aulia; Fandiyanto, Randika; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the analysis of factors that influence job satisfaction of non-ASN employees of the Cooperatives, Industry and Trade Service of Situbondo Regency with work effectiveness as a mediating variable. Using the Partial Least Square (PLS) Structural Equation Model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Career Development has a significant positive effect on Work Effectiveness, Work Performance has a significant positive effect on Work Effectiveness, Employee Performance has a significant positive effect on Work Effectiveness, Career Development has a positive but not significant effect on Job Satisfaction, Work Performance has a significant positive effect on Job Satisfaction, Employee Performance has a positive but not significant effect on Job Satisfaction, Work Effectiveness has a significant positive effect on Job Satisfaction, Career Development on Job Satisfaction through Work Effectiveness has a positive but not significant effect, Work Performance on Job Satisfaction through Work Effectiveness has a significant positive effect, Employee Performance on Job Satisfaction through Work Effectiveness has a significant positive effect.